'It's as if you're not in the Jail, as if you're not a Prisoner': Young Male Offenders' Experiences of Incarceration, Prison Chaplaincy, Religion and Spirituality in Scotland and Denmark. Issue 1 (11th March 2016) - DEUCHAR, ROSS; MØRCK, LINE LERCHE; MATEMBA, YONAH HISBON; MCLEAN, ROBERT; RIAZ, NIGHET
Abstract: This article explores Scottish and Danish young male offenders' experiences of incarceration, prison chaplaincy, religion and spirituality. The findings from in‐depth face‐to‐face semi‐structured interviews (n = 15) suggest that although Scotland and Denmark are increasingly secular countries, the prison environment (deprivation of liberty, vulnerability and feelings of guilt) seems to engender pro‐religious/spiritual attitudes and an interest in prison chaplaincy services. Working with interfaith chaplains enabled the young inmates to take small steps towards managing the social strains that led them into offending, and the 'painful' experiences they encountered during imprisonment. The holistic chaplaincy services that they were offered helped to nurture some initial turning points that stimulated identity and behaviour change linked to transitional masculinity, and in some cases to an increased commitment towards criminal desistance.